PENINGKATAN PENGETAHUAN PAKAN TERNAK BERBASIS HERMENTIA ILLUCENS (MAGGOT BSF) DI PONDOK PESANTREN DAARUL HAWARIYIN - Rimantho, Dino; Sandy, Anggina; Ariyani, Dwi (Abdi Implementasi Pancasila:Jurnal Pengabdian kepada Masyarakat, 2025)
The high demand for animal feed and the high price of animal feed pellets on the market are challenges faced by the community, especially chicken and catfish farmers. Providing animal feed to the community is crucial for the sustainability of chicken and catfish production. Daarul Hawariyin Islamic Boarding School is one educational institution experiencing difficulties in managing animal feed needs. Al Hikmah Islamic Boarding School still uses manufactured animal feed, resulting in significant operational costs. Therefore, the goal of this community service program is to increase knowledge about the use of BSF maggots as a source of animal feed. As part of the community service project, several selected religious teachers (ustadz) participated in capacity-building training on animal feed. Participants received questionnaires before and after the training. The questionnaires consisted of two categories: cognitive and affective. The results showed a significant difference in the cognitive category and no significant difference in the affective category.